ANALISIS POTENSI OBJEK DAYA TARIK WISATA ALAM DI DESA DELUK KECAMATAN BANTAN KABUPATEN BENGKALIS - Diah Paramita Sari; M. Sabri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
This research aimed to analyze the natural tourism objects and attractions and also the supporting facilities which are available in Deluk village to measure the feasibility level of the village to be developed into a tourism area. The methodology used for this research was a descriptive quantitative. The data needed for this research were collected through direct observation towards some natural tourism objects in the village and also through interview with related stakeholders. The data were then analyzed based on the guidelines given by General Directorate of Forest Reserve and Nature Conservation (PHKA) of 2003. After doing the research and analyzing the data, it can be concluded that Deluk village of Bantan Subdistrict of Bengkalis Regency has such proper potency so that it is ‘feasible’ to be developed into a tourism area. However, other factors such as the community readiness, the tourist opinion and the government support are still needed to be observed to get a more holistic recommendation.